Use of GeneXpert for the diagnosis of multidrug resistant pulmonary tuberculosis among smear negative suspected tuberculosis cases in Nepal (Janaki Medical College Journal of Medical Science, 2017)
Not Available.Janaki Medical College Journal of Medical Sciences (2016) Vol. 4 (2): 50-52